Behavioral Problems of Learners in Iba District, Zambales: Basis for an Intervention Plan - Magtalas, Santi A.; Bundang, Emma T. (Future Science / FSH-PH Publications, 2025)
This descriptive-correlational study surveyed 150 elementary teachers in Iba District, Zambales using a validated questionnaire. Results revealed that learners with behavioral issues generally performed fairly satisfactory (M=79). Common behaviors included indifference, lack of motivation, violent tendencies, destructiveness, and communication problems. Misbehavior significantly correlated with impacts on teaching (r=.756), classroom management (r=.724), academic success (r=.786), and school climate (r=.658). Teachers strongly endorsed preventive, intramural support, and communication strategies. An intervention plan is recommended involving teacher training, parental engagement, and structured behavioral programs.